If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + -23 = 3x + 16 Reorder the terms: -23 + 4x = 3x + 16 Reorder the terms: -23 + 4x = 16 + 3x Solving -23 + 4x = 16 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. -23 + 4x + -3x = 16 + 3x + -3x Combine like terms: 4x + -3x = 1x -23 + 1x = 16 + 3x + -3x Combine like terms: 3x + -3x = 0 -23 + 1x = 16 + 0 -23 + 1x = 16 Add '23' to each side of the equation. -23 + 23 + 1x = 16 + 23 Combine like terms: -23 + 23 = 0 0 + 1x = 16 + 23 1x = 16 + 23 Combine like terms: 16 + 23 = 39 1x = 39 Divide each side by '1'. x = 39 Simplifying x = 39
| 6=2(1+w) | | 500=4x^2-40x+400 | | 2(x-12)=27 | | 9(m-3)=5m+9 | | 5(2a+7)=2(3a+4) | | 815/12=a | | 16+3x=19+21x | | -27.083x-16.819=-11.246 | | x+91=x+97 | | 11e=9e+4 | | 5+2x=9.50 | | 4d^2+64=0 | | 2x-3x=14 | | -3n+11-7n=-13 | | 2z-1=z+8-22 | | x+91=x+971 | | x^2-22xy-48y^2= | | x/4-10=-13 | | -3+11-7n=-13 | | 6c-12+4c=8c | | -3+9=a | | 81-(6*9)=1 | | 19f^2-17k-2=0 | | 3s-4+6s+7= | | 18x^2+9x-20=0 | | d^2-14d+13=0 | | -6/5=a | | 16x-5=105 | | -5(4r+8)=16-3r | | (7x+2)(3x^3-14x-5)=0 | | 7x=434 | | 12+1234567890=x(43+83) |